"Who Keeps Your Flame? Who Tells Your Story?" Teaching Orchestra through Primary Sources. (December 2022) - Davis, Susan A.
Music educators often look for ways to deepen students' understanding and artistic interpretations of repertoire. One way to engage students in discovery and dialogue about the music they perform is through connecting to the historical, cultural, and societal implications of primary sources. This article delves into resources from the Library of Congress that enable us to tell richer stories about the people and circumstances behind familiar orchestral repertoire, including works by Chaminade, Copland, and Miranda. The recommended materials include primary and secondary sources from the Library of Congress digital archives, best practices for using these resources, inquiry-based strategies to engage students in critical thinking, and connections to the 2014 Music Standards.